Macrofauna bentônica de substratos móveis dos manguezais do estuário do rio Paciência sob impacto das atividades humanas, ilha de São Luís, Maranhão, Brasil - RODRIGUES, Hinayara Rodrigues Barros (2011)
The study aimed to integrate indicators of water quality with indicators of human health in the estuary. It was adopted a multipronged approach, including physical and chemical parameters of water, biological indicators (benthic macroinvertebrates) and human health indicators (deaths from waterborne diseases). The organisms were collected with the help of a PVC pipe, with an a sample area of 0.0079 cm2, then fixed in 4% formalin, preserved in 70% alcohol and later identified to the lowest taxonomic level possible with the aid of literature specialized. The physical-chemical analysis of water was performed with a kit multiparameter model HQ40d. And microbiological analysis were performed according to the technique of multiple tubes. For particle size analysis it was used the gravimetric technique. Macrobenthic species were more abundant during the rainy season, being the Neanthes succinea, the most representative specie. Values were considered high for nitrate, phosphate, total and thermotolerant coliforms to a balanced environment. In the points where this fact happened, the Neanthes succinea species was dominant, demonstrating the ability of this species to resist a disturbed environments, showing that the specie is a bioindicator. Based on the results, it is possible to infer that the poor water quality affects the health of the population and composition of aquatic biological communities. Into the total of the nine species identified in this study, five are considered bioindicators, they are: Neanthes succinea, Capitella capitata, Laeonereis acuta, Mytella charruana e Anomalocardia brasiliana. The integration of multiple indicators in determining the health status of coastal communities is a fundamental contribution to basic sanitation programs. The evaluation of multiple indicators, including abiotic parameters, biological, epidemiological and ground occupation, proved be more useful for a most realistic understanding of degradation processes on the estuary of Paciência river and its implications on public health of this estuary environment.